Coalitional cohesion in technology policy: The case of the early solar cell industry in the United States - Timur Ergen (Max Planck Institute for the Study of Societies, 2017)
The paper traces the rise and decline of solar cell commercialization efforts during the 1970s and early 1980s in the United States. It shows how technology policies for photovoltaic appliances gained and lost support in a time of increasing uncertainty about future resource supplies and the future of energy provision. Contrary to conventional explanations of the long history of failures to commercialize renewable energy technologies that emphasize path dependencies around established energy technologies, this paper explains the rise and decline of early solar cell policies from the perspective of internal sectoral developments. It demonstrates that cohesion among political economic supporters was critical for public perceptions of the intermediary success of the effort, to continuous investment by industry, and to the maintenance of political support. The paper suggests that support for new industries and technologies is dependent on sectoral order among supporting groups over time. The case of the early photovoltaics policies illustrates how the failure to keep groups unified and committed undermined the implementation of the technology policies, weakened the credibility of the developmental effort, and ultimately led to a decline in political support. The paper contributes to recent debates about the conditions of successful industrial and technology policies by demonstrating that network failures have an important political dimension if ruptures of sectoral cooperation feed back on state support for the respective industry or technology. – – Der Aufsatz zeichnet den Aufstieg und Niedergang früher Kommerzialisierungsinitiativen für Solarzellen in den USA während der 1970er- und 1980er-Jahre nach. Er erklärt, warum Förderprogramme für Photovoltaikanlagen in einer Zeit wachsender Unsicherheit über die zukünftige Gestalt von Energieversorgungssystemen Unterstützung erhielten und wieder verloren. Im Unterschied zu konventionellen Erklärungen der Geschichte von Fehlschlägen in der Kommerzialisierung von Solartechnologien, die größtenteils die Beharrungskräften etablierter Energieerzeugungssysteme herausstellen, fokussiert der Aufsatz interne sektorale Entwicklungen. Er zeigt, dass Kohäsion unter Unterstützern kritisch für die Wahrnehmung der Effektivität der Unterstützungsprogramme, für kontinuierliche Industrieinvestitionen und für die Stabilität staatlicher Förderung war. Der Fall der frühen Photovoltaikprogramme zeigt, dass nachlassender Zusammenhalt unter beteiligten Akteuren die Implementation der Unterstützungsprogramme und die Glaubwürdigkeit des Entwicklungsanlaufs untergraben hat und letztlich zum Abflauen staatlicher Förderung führte. Der Aufsatz trägt zu neueren Debatten über die Bedingungen erfolgreicher Industrie- und Technologiepolitik bei, indem er zeigt, dass industrielle "Netzwerkfehler" eine politische Dimension haben, sobald Unterbrechungen sektoraler Kooperation auf die staatliche Unterstützungsbereitschaft zurückwirken.
hdl:11858/00-001M-0000-002D-6E07-7
Keywords: 300; technology policy; renewable energy; institutional change; governance; innovation; Technologiepolitik; erneuerbare Energien; institutioneller Wandel; Governance; Innovation